2015
DOI: 10.1590/s1413-70542015000200003
|View full text |Cite
|
Sign up to set email alerts
|

COMPETITIVE ABILITY OF WHEAT IN ASSOCIATION WITH BIOTYPES OF Raphanus raphanistrum L. RESISTANT AND SUSCEPTIBLE TO ALS-INHIBITOR HERBICIDES

Abstract: The occurrence of Raphanus raphanistrum ALS herbicide-resistant in wheat crops causes crop yield losses, which makes it necessary to understand the factors that influence the interference of this weed to develop safer management strategies. This study aimed to evaluate the competitive ability of wheat in coexistence with biotypes of R. raphanistrum that are resistant (R biotype) and susceptible (S biotypes) to ALS herbicides and to determine whether there are differences in the competitiveness of these biotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
2
8
0
1
Order By: Relevance
“…Therefore, it is observed that interspecific competition is less harmful than intraspecific competition for both species involved. When working with rice and soybean x zigzag jointvetch (Aeschynomene rudis) (Agostinetto et al, 2013), wheat x turnip 8 (Costa and Rizzardi, 2015), rice in competition with zigzag jointvetch (Aeschynomene rudis) (Galon et al, 2015) and wheat in the presence of ryegrass (Rigoli et al, 2008), the same effects denoted in this study were also observed.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Therefore, it is observed that interspecific competition is less harmful than intraspecific competition for both species involved. When working with rice and soybean x zigzag jointvetch (Aeschynomene rudis) (Agostinetto et al, 2013), wheat x turnip 8 (Costa and Rizzardi, 2015), rice in competition with zigzag jointvetch (Aeschynomene rudis) (Galon et al, 2015) and wheat in the presence of ryegrass (Rigoli et al, 2008), the same effects denoted in this study were also observed.…”
Section: Resultssupporting
confidence: 84%
“…The knowledge of the dynamics and competitiveness between plants -especially barley and turnip -is essential for decision-making to control the weed in a given population that will not cause negative interference on the culture, even considering that the turnip can produce up to 17,275 seeds m -2 (Reeves et al, 1981) and that this weed is resistant to the herbicides inhibiting ALS (Costa and Rizzardi, 2015), widely used in controlling infesting weed species of barley and wheat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the variable of onion leaf area the competition with turnip was much more aggressive when compared to competition with ryegrass (Figure 3A and 3B). Competitive potential of turnip was observed in relation to ryegrass when these two weeds infested winter cereals (Costa and Rizzardi, 2015). There was a significant reduction in leaf area values of onion in the lowest established competition (one plant pot -1 ).…”
Section: Resultsmentioning
confidence: 96%
“…This fact is due to the high prolificacy, longevity, seed dormancy and germination capacity under adverse conditions of climate and soil. It was found that this species has a competitive capacity of 5 to 10 times greater than ryegrass (Lolium multiflorum) when in competition with winter cereals (Costa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%